Five new Amphibolips Reinhard, 1865 (Hymenoptera, Cynipidae) species from western and southern Mexico: expanding the diversity of oak gall wasps and revealing the largest oak apple gall in the Americas - Castillejos-Lemus, Dohuglas Eliseo; Oyama, Ken; Zhang, Y. Miles; Valencia-A, Susana; Nieves-Aldrey, José Luis (Zootaxa, 2026)
Five new species of oak gall wasps of the genus Amphibolips Reinhard, 1865 (Cynipidae, Cynipini) are described from Mexico. Amphibolips megalokokka Nieves-Aldrey & Castillejos-Lemus sp. nov. and Amphibolips oyamai Castillejos-Lemus & Nieves-Aldrey sp. nov. from the Trans-Mexican Volcanic Belt (TMVB) exhibit unique morphological characteristics within the genus, particularly in gall morphology. Three additional species, Amphibolips zapoteco Nieves-Aldrey & Castillejos-Lemus sp. nov., Amphibolips idiopteryx Nieves-Aldrey & Castillejos-Lemus sp. nov. and Amphibolips darioi Castillejos-Lemus & Nieves-Aldrey sp. nov., are described from Oaxaca State. These Oaxacan species show remarkable morphological similarity while providing important insights into the relationships among species within the Oaxacan clade. Based on a prior phylogenetic study using ultraconserved elements, we describe these five new species with supporting evidence from both morphology and molecular data. We also examined the great morphological variation in Trans-Mexican Volcanic Belt species, including both generations of one species, and discusses species richness, phylogenetic relationships, and taxonomic challenges within the genus.